Aménagement du territoire et sociologie - Dumont, Fernand; Martin, Yves (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1961)
Sociology as a science does not deal with social variables considered individually, but, essentially, with the structuration process that is inherent in any social structure seen as an integrated whole. The sociological approach to regional analysis is defined, by the authors, with reference to that observation on the methodology of their discipline. A discussion is presented about two disciplines that have been developed by sociologists as attempts to provide a frame of reference for the study of relationships between man and his environment : « Social morphology, » a creation of the French School of sociology, with Durkheim, Mauss and Halbwachs ; and « Human ecology, » whose origins, with Park and Burgess, and further develop-ments are an almost exclusively American phenomenon. Finally, the authors express their views about a sociological interpretation of the concept of region, their argument being that the elaboration of a specifically sociological theory of the region should be the first step towards a systematic integration of spatial variables in sociological analysis.